Pengaruh Pemberian Stimulasi pada Perkembangan Anak Usia 12-36 Bulan di Kecamatan Sedayu, Bantul - Febrina Suci Hati; Prasetya Lestari (Alma Ata University Press, 2016)
The important period during the growth of children is the ﬁ rst ﬁ ve years which is the golden period of life. Stimulation has important roles to improve child growth and development, especially cognitive function, psychomotor and affective. The lack of stimulation will result in the loss of function of the brain cells. Stimulations from parents and nutritional status are two factors which inﬂuence children’s growth. The purpose of this study was to identify the relation between development stimulation in 1-3 years old children. The research used analitic prospectif cohort in 1-3 year old children in Sedayu Sub-District, Bantul Regency from February until May 2015. The sampling technique used was cluster sampling. The instruments used were questionnaire, and KPSP form. Univariate data analysis technique used frequency distribution, bivariate analysis used Spearman’s rank, There was a signiﬁ cant relation between stimulation and development children in 1-3 years old (p=0,001; CI 95% ;OR=3,37).